Economic Appraisal of Date Palm Plantations in Western Rajasthan - Bhati, G N; Kalla, Jagdeesh C; Vyas, D L (Annals of Arid Zone, 2016)
Date palm plantations offer an attractive arid land use option where irrigation water, sunshine and absence of rainfall at fruit ripening. stage Form natural resource endowments. Economic analysis of the date palm plantations in arid areas of western Rajasthan revealed that estimated IRR was only 13 percent, being little less than the prevalent bank interest rate of 14 percent per annum on long-term investment, The results rendered this enterprise little short of economic viability. The viability could however. be enhanced by incorporating under-storey companion crops or vegetables under irrigated conditions together with combining production and processing of fruits, and providing liberal institutional help.